What do Cats do All Day? - Bordewick, Megan; Marshall, Jeremy L. (My University, 2017)
When we look at zoo animals, we only see them for a couple of minutes at most. We do not see how active they really are, nor do we get a good representation of their behavior (Szokalski et al 2012; Allen et al. 2015). Cats are usually seen as lazy, sleepy animals. However, what do zoo cats really do during the day? Following four separate visits of 70 minutes each, the results showed a correlation between social behavior/movement based on size of the animal. There is a clear difference in the level of activity and observable behaviors among these species of big cat. The data suggest that smaller cats, like the Bobcat may be better at showing the public a wider range of behaviors.